Metal-free polymer/MWCNT composite fiber as an efficient counter electrode in fiber shape dye-sensitized solar cells - Ali, Abid; Shah, Syed Mujtaba; Bozar, Sinem; Kazici, Mehmet; Keskin, Bahadir; Kaleli, Murat; Akyurekli, Salih; Gunes, Serap (IOP PUBLISHING LTD, 2016)
Highly aligned multiwall carbon nanotubes (MWCNT) as fiber were modified with a conducting polymer via a simple dip coating method. Modified MWCNT exhibited admirable improvement in electrocatalytic activity for the reduction of tri-iodide in dye sensitized solar cells. Scanning electron microscopy images confirm the successful deposition of polymer on MWCNT. Cyclic voltammetry, square wave voltammetry and electrochemical impedance spectroscopy studies were carried out to investigate the inner mechanism for the charge transfer behaviour. Results from bare and modified electrodes revealed that the MWCNT/(poly (3,4-ethylene dioxythiophene): poly(styrene sulfonate) (PEDOT:PSS) composite electrode is much better at catalysing the I-3(-)/I- redox couple compared to the pristine fiber electrode. The photoelectric conversion efficiency of 5.03% for the modified MWCNT electrodes was comparable with that of the conventional Pt-based electrode. The scientific results of this study reveal that MWCNT/PEDOT: PSS may be a better choice for the replacement of cost intensive electrode materials such as platinum. Good performance even after bending up to 90 degrees and in-series connection to enhance the output voltage were also successfully achieved, highlighting the practical application of this novel device.
Keywords: metal free polymer/MWCNT fiber; fiber shape dye sensitized solar cells; PEDOT:PSS modified counter electrode; ALIGNED CARBON NANOTUBES; WIRE; SUPERCAPACITORS; Science & Technology - Other Topics; Materials Science; Physics